IRON STATUS OF THE STUDENTS OF AYUB MEDICAL COLLEGE - Alamgir, Afzal; Yousuf, Muhammad; Badar, Ahmed; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 1999)
The concern about the iron status of an individual traditionally rotates around the finding of anemia. However, some recent studies are suggestive of many other symptoms of iron deficiency which can be present even before the iron deficiency anemia appears. The purpose of this study was to determine the iron status of the students of Ayub Medical College by determining serum ferritin that is the best investigation to determine the stored iron. We found that 8.42 % of the male students and 13.68 % of the female students were iron depleted, while just 4.2 J % males and 8.42 % females were anemic. This suggests that iron deficiency in absence of anemia is present in our students.